Quality of Life in Spinal Cord Injury: Experience at a Military Tertiary Care Hospital - Khan, Omer Jamshed; Ansari, WafaMunir; Ahmed, Nadeem (International Journal of Pathology, 2018)
Background: Spinal Cord Injury can have devastating consequences on an individual’s physical and social capabilities. There is a scarcity of studies in Pakistan which identify the factors having a favorable and unfavorable effect on Quality of Life.Objective: Determine the mean satisfaction score using Quality of life and Visual Analogue Scale scores in patients with Spinal Cord Injury.Methods: The study was carried out for 6 months at the Armed Forces Institute of Rehabilitation Medicine (AFIRM), Rawalpindi. Total of 60 patients of SCI, both male and female were recruited by consecutive (non-probability) sampling. Quality of life and Visual Analogue Scale were measured using the Euro Quality o flife questionnaire. Data was analyzed using SPSS 17.Results: The cross sectional descriptive study included 60 patients 49 (81.7%) males and 11 (18.3%) females. The average age in the study group was 32.37 ± 10 years. The mean duration of injury was 11.5 months ± 5.18. Employment status, level of education and duration of injury had moderately significant (p<0.05) effect while type of injury had a highly significant (p<0.01) effect on Quality of life and in Spinal cord injury patients. Age, marital status and gender did not have any significant influence on QoL in these patients. VAS score was significantly higher (p=0.002) in SCI patients with incomplete injury as compared to those with complete injury.Conclusion: Spinal cord injury rehabilitation greatly impacts outcome scores. Patient satisfaction can be improved by educating and guiding the patient . Standardized tools need to be used to measure rehab outcomes.